2014
DOI: 10.3892/ijo.2014.2811
|View full text |Cite
|
Sign up to set email alerts
|

LH-RH analogues in the treatment of young women with early breast cancer: Long-term follow-up of a phase II study

Abstract: Abstract. To prevent premature ovarian failure (POF), high-risk, premenopausal women with early breast cancer were given a luteinizing-hormone releasing hormone (LH-RH) analogue during adjuvant chemotherapy. After an adriamycin-based regimen, patients received radiation therapy concomitant with cyclophosphamide, methotrexate and 5-fluorouracil. An aromatase inhibitor was given to patients positive for the estrogen receptor (ER + ). The median age was 43 years (range, 26-45). Among 200 consecutive patients, 46%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Most studies that were observational, non‐randomized or in which oral contraceptives were used were excluded at the abstract screening phase (Figure ). Of the 11 articles that were excluded after full‐text review, two were retrospective studies, two were registered but not completed (NCT02483767 and NCT02430103), one included oral contraceptives in the control group, one was not randomized, two recruited historical controls, one did not include controls and two presented partial results of studies published later in complete version.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies that were observational, non‐randomized or in which oral contraceptives were used were excluded at the abstract screening phase (Figure ). Of the 11 articles that were excluded after full‐text review, two were retrospective studies, two were registered but not completed (NCT02483767 and NCT02430103), one included oral contraceptives in the control group, one was not randomized, two recruited historical controls, one did not include controls and two presented partial results of studies published later in complete version.…”
Section: Resultsmentioning
confidence: 99%
“…A study with women with BC in CT found an immediate reduction of ovarian blood flow after treatment, demonstrating a postmenopausal profile for most patients accompanied by related symptoms [60]. Thus, those perimenopause women who do CT, especially with anthracycline-based regimens compared to CMF [61], may enter menopause more frequently with CT and present earlier and induced symptoms already known from climacteric, such as changes in body composition [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…1,4-9,13-15,19-37 Therefore, this noninvasive and inexpensive treatment has gained ubiquitous interest and popularity. 1,4-9,13-15,19…”
Section: Past and Present Experience Using Gnrh Analogs For Fertilitymentioning
confidence: 99%